Effectiveness of planned teaching programme on knowledge and practice regarding secondary survey of trauma patients among trauma nursing officers - Khuswaha, Sheela; Yadav, Rakhi; Bairwa, Kamlesh; Sarkar, Bhaskar (International Journal Of Community Medicine And Public Health, 2024)
Background: Secondary survey is crucial for quickly and methodically evaluating damaged patients from head to toe, discovering any injuries that were underlooked in the first survey, and quickly and methodically evaluating polytrauma patients when it’s unclear what’s causing their symptoms. The study aimed to assess the knowledge and practice of secondary survey in nursing officers in AIIMS Rishikesh. Methods: This pre-experimental (one group pre-test and post test research) study was conducted to assess the effectiveness of planned teaching programme. 30 minutes of secondary survey class followed by demonstration of same. Using non- probability convenient sampling technique, total of 133 nursing officers were selected from Trauma Center of AIIMS Rishikesh. Self structured questionnaire was given to participants and practice was assessed using practice checklist. Results: The pre-test and post-test mean knowledge was found 14.08 and 18.40 and mean practice was 12.51 and 31.11 indicating the enhancement of knowledge and practice (tcal 130.28 >t table1.98 at p <0.05). Difference between pre-test knowledge (14.08±2.455) and Pre-test practice (12.51±5.188) indicate adequate knowledge with inadequate practice. Conclusions: The study concluded that the secondary survey knowledge and practice improves with adequate guidance and information. So, there is need for regular training session for trauma nursing officers to sustain this information and practice enhancement can be done by regularly implementing practice checklist in documentation.